EFFECT OF INTELLIGENCE QUOTIENT, EMOTIONAL QUOTIENT TOWARD PERFORMANCE THROUGH SPIRITUAL QUOTIENT - Sugianta Ovinus Ginting; Nasrul Efendi; Purnaya Sari Br. Tarigan (Universitas Pendidikan Nasional, 2020)
Each company needs some foundation in order to develop in the future, between the foundation is the quality of human resources that enable them to formulate and implement any strategies and use various technologies to achieve the goal. This research aims to determine the impact of the intelligence quotient, emotional quotient through employee performance on spiritual question as an intervening variable. The sampling technique using probability sampling with simple random sampling approach with a sample of 84 employees. The data obtained has fulfilled the validity test, reliability test and processed using path analysis equation to determine the direct and indirect impact on the independent variables through the dependent variable. The findings of this research show that partially the intellectual intelligence has a significant impact on the variables of spiritual intelligence but it does not directly has impact on the employee performance, emotional intelligence partially has a significant impact on spiritual intelligence variables but it doesn’t directly has impact on the employee performance, spiritual intelligence has a significant direct impact on the employee performance and Simultaneously the intellectual intelligence, emotional intelligence or spiritual intelligence have impact on the employee performance and intellectual intelligence, emotional intelligence have a significant impact on the employee performance through the employee spiritual intelligence.